2006
DOI: 10.1103/physrevlett.96.031302
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Evaporation of a Naked Singularity

Abstract: We investigate here quantum effects in gravitational collapse of a scalar field model which classically leads to a naked singularity. We show that nonperturbative semiclassical modifications near the singularity, based on loop quantum gravity, give rise to a strong outward flux of energy. This leads to the dissolution of the collapsing cloud before the singularity can form. Quantum gravitational effects thus censor naked singularities by avoiding their formation. Further, quantum gravity induced mass flux has … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
115
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 123 publications
(118 citation statements)
references
References 28 publications
3
115
0
Order By: Relevance
“…From observational point of view it was shown that the near extremal naked singularities can host ultra-high energy particle collisions and thus can serve as an astrophysical probe of high energy physics [16][17][18][19][20]. We also note that there are many investigations where it is demonstrated that the naked singularities can form as an end-state of the continual gravitational collapse [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…From observational point of view it was shown that the near extremal naked singularities can host ultra-high energy particle collisions and thus can serve as an astrophysical probe of high energy physics [16][17][18][19][20]. We also note that there are many investigations where it is demonstrated that the naked singularities can form as an end-state of the continual gravitational collapse [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence of η being constant there will be a maximum areal radius for the star (see figure 2) that turns out to be too small to model any astrophysical object. Anyhow, we can consider the power-law behaviour as an approximation valid only around the collapsing event and obtain the evolution of the star's surface around R = 0 from the evolution equation (42) and with the help of (39). This has to be done numerically and the result, which is qualitatively similar for all the allowed values for n, is shown in figure 3.…”
Section: Interiors Dominated By a Scalar Fieldmentioning
confidence: 99%
“…a(t), we can obtain L ∞ as a function of t through the matching conditions (39)(40)(41)(42) and, after some algebraic manipulation, we can write it in the useful form…”
Section: Measured Luminositymentioning
confidence: 99%
“…Moreover, if naked singularities would exist in nature, then the cosmic censorship hypothesis would not hold. Numerical calculations and some other arguments have also hinted at this possibility [28][29][30][31][32][33]. For example in [34] the possibility of strong causality violation in the presence of a naked singularity has been analyzed.…”
mentioning
confidence: 99%